Absence of a prezygotic behavioural barrier to gene flow between the two sympatric morphs of the squat lobster Munida gregaria (Fabricius, 1793) (Decapoda: Anomura: Galatheidae) - Pérez-Barros, P. (2011)
Munida gregaria and M. subrugosa have been considered two different species for more than a century; however, after a recent molecular phylogenetic study, they are considered a single polymorphic species. Yet, the use of markers to diagnose species may be misleading when divergence between species is recent, since a speciation event may be obscured by the retention and stochastic sorting of ancestral polymorphisms. The morphs gregaria and subrugosa of Munida gregaria constitute an interesting case for the study of behavioural isolation since they are sympatric, breed at the same time of the year, and might have experienced a recent speciation. Mating behaviour observations and mate choice mating trials were conducted in order to investigate the potential existence of a behavioural prezygotic barrier to gene flow between these two morphs. Since factors involved in mate choice in galatheids are unknown, the four possible combinations of the two different morphs in trios were used to test for the existence of mate choice. Video recordings of all the possible trio combinations revealed that there was cross-attraction between males and females of different morphs. Females bearing partial broods participated in encounters as well as non-ovigerous females. The frequency and duration of homo- and heterotypic encounters were registered, and a reproductive isolation index was calculated for each variable for each trio. The isolation indexes calculated were not different from zero indicating random mating, and were not affected by the composition of the trio or the partial ovigerous condition of females. These results provided evidence of the absence of behavioural prezygotic barriers to gene flow between the morphs gregaria and subrugosa of M. gregaria. © 2011 Springer-Verlag and AWI.